Determinants of Tax Aggressivity in Food and Beverage Sub-Sector Companies on The Indonesian Stock Exchange - Tambunan, Martua E.; Samaria, Angel (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Tax is an obligation that must be fulfilled by companies to the state. In fulfilling their tax obligations, companies often engage in tax aggressiveness to minimize the tax burden they must pay. This study aims to examine and analyze the influence of factors such as profitability, leverage, company size, and corporate social responsibility on tax aggressiveness in the food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the period from 2019 to 2021. This research uses a quantitative approach with data collection through documentation, where the researcher analyzes the financial statements of the companies listed as samples. The data analysis method used is panel data regression to test the proposed hypotheses. The sampling technique employed is non-probability sampling with a purposive sampling approach, selecting 16 companies as the sample, resulting in 48 observations. The results show that profitability has a negative and significant effect on tax aggressiveness. Leverage and company size do not have a significant effect on tax aggressiveness, while corporate social responsibility has a significant negative effect on tax aggressiveness. This study provides valuable insights for companies and regulators regarding the factors that may influence tax behavior in the food and beverage industry.